Evaluation of the fatal accident factors in the petroleum industry using hybrid Gaussian multi-criteria decision -making (MCDM) approach. Issue 1 (31st December 2022) - Wicaksono, Fermi Dwi; Ciptomulyono, Udisubakti; Artana, Ketut Buda; Irawan, Mohammad Isa
Abstract: The petroleum industry possesses highly complex operation involving several organizational functions, which are different occupationally, i.e., drilling operation, logistic and material supply chain, offshore construction, and facilities maintenance operation. This circumstance prompts critical risks of fatal accident occurrence, which needs to be identified for further incident prevention. Accident causing factors analysis needs to be conducted for the primary accident prevention measures. This paper demonstrates the quantitative analyses by evaluating fatal accident causing factors by implementing an improved method of multi-criteria decision-making. The hybrid technique of structural equation modeling, Gaussian fuzzy decision-making trial and evaluation laboratory, and Gaussian fuzzy Monte-Carlo analytic network process. This study discloses that human factor comes as the first significant causing factors that prompt to fatal accident in the petroleum industry with the value of 0.3015. As the second place, the management system dysfunction lies with the value of 0.3006. And lastly, occupational and working condition factor with the significance value of 0.2956. In terms of risks quantification, maintenance and production operations is evaluated as the most high-risk activity with the value of 0.136. The Gaussian fuzzy number and Monte-Carlo technique in this study are able to evaluate the fatal accident causing factors' uncertainty of evaluations.